Analysis of Writing Styles in Bi Al-Ma'tsur's Tafsir Books - Alim Mujahidin; Abdul Matin bin Salman (Penerbit Hellow Pustaka, 2024)
Tafsir Bi Al-Ma'tsur is explaining the meaning of the verses of the Qur'an with verses from the Qur'an or authentic Sunnah verses or the words of the companions of R.A. While the words narrated from the Tabi'in, some people classify them as al-ma'tsur on the grounds that the Tabi'in narrated from friends who studied with them, they also belong to the group of Salaf whose good words and interpretations adorn tafsir books such as the book of Ibn Jarir al- tabary and anyone who follows his method. Tafsir Bi Al-Ma'tsur existed during the time of the Companions, which was carried out by quoting interpretations from Rasulullah SAW, or from the Companions by the Companions, as well as from the Companions by the Tabi'in with a clear method of narration, this method is usually done orally. After that there was a period where the interpreters used the exegesis of the Companions' time which had been recorded and codified. At first this codification was included in the hadith books, but after tafsir became a separate scientific discipline, books were written and published specifically containing the Tafsir of Bi Al-Ma. 'tsur complete with sanad lines to the prophet Muhammad SAW, his companions, tabi'in al tabi'in.